La lógica donal: Un estudio desde San Agustín y Leonardo Polo - Munive Hernández, Edgard (Mercurio Peruano, 2020)
One of the contributions of transcendental anthropology of Leonardo Polo is the distinction between human nature and human person. An antecedent is found in the Privacy Anthropology of St. Augustine. Augustine distinguishes in man spirit, soul and body, according Polo, the spirit would be the person.The donal logic is the logic of people. Along history, we can distinguish two types of logic of human action: classical logic, where activities related to self-improvement are prioritized and modern logic, focusing on those activities that have to do with changing the nature. Instead, the logic donal focuses on those activities concerning improvement of others. If classical logic focuses on virtue and modern logic on produce; donal logic will focus on the gift.
Keywords: English; logic, gift, love, transcendental, person, reciprocity, interiority